Mapping flows of blue economy finance: Ambitious narratives, opaque actions, and social equity risks - Schutter, Marleen; Cisneros-Montemayor, Andrés; Voyer, Michelle; Allison, Edward (Eddie); Domarchuck-White, Calvin; Benzaken, Dominique; Mohammed, Essam Yassin (Cell Press, 2024)
The blue economy provides a sustainability framework for ocean governance, but it is unclear whether narratives are matched by binding financial commitments and disbursements. Amid attention being paid to “funding gaps” in the Sustainable Development Goals, a lack of transparency in financial flows means that the blue economy concept risks being co-opted to facilitate further exploitation of ocean spaces and resources without contributing to environmental sustainability or social equity. Here, we analyze blue-economy-labeled money flows disbursed between 2017 and 2021 to identify sources and recipients and potential social equity impacts on the ground. Financing is predominantly disbursed to Europe and Central Asia and skewed toward business development and renewable energy. Our analysis reveals widespread occurrence of “red flags” for social equity outcomes. Although constrained to money flows that actively employ blue economy language, our findings show disconnects between finance and narratives of equity, inclusion, and sustainability. We offer a baseline for critical examination of blue finance flows in delivering equity and environmental sustainability.